Genome-wide Comparative Analysis In Discovering Potential Evolved Hypothetical Genes In Infected Oil Palm - Suhaila Sulaiman; Nur Syamimi Yusoff; Lee Yang Ping (Malaysian Society of Applied Biology, 2024)
Based on the genome annotation, oil palm genes can have either known or unknown functions. Hypothetical genes or unknown genes constitute averagely 24.40% from three gene model versions of oil palm (Elaeis guineensis Jacq.). The conventional method to prove their existence is labourious and limited, thus by bioinformatics analysis of genomic and transcriptomicdata, the potential role of hypothetical genes can be scrutinised comprehensively. In this study, the annotated hypotheticalgenes are reanalysed using sequence-based and transcriptomic data analysis to investigate their presence, differential expression and potential horizontal gene transfer (HGT) event with distantly related organisms in infected oil palm. In total 610 sequences still remain as hypothetical whilst others showed similarities with known genes which are not considered as hypothetical anymore. From the 610 genes, 92 are conserved in model plants and non-Plantae and eight genes are potential candidates of HGT events in oil palm with changes of expression during Ganoderma boninense infection. A transferred gene usually possess critical function, thus the presence of true hypothetical genes should not be ignored since it can be served as potential biomarkers of desired traits in oil palm.